Successful management of juvenile residential facilities: a performance-based approach - Heinz, Joseph W. (American Correctional Association, 2010)
A brief history of institutional care for juveniles -- A profile of youth in juvenile residential correctional facilities -- Managerial styles and institutional control -- Why mission is important -- How institutional management fulfills the mission-administrator's duties -- The administrator's role in treatment -- The administrator's role in building positive culture -- Staff training -- Models of institutional care